Case report and literature review: cardiac hematic cyst - Baltodano-Arellano, Roberto; Alvarez-Tiburcio, Eduardo; Barriales-Revilla, Lucia; Bellido-Yarlequé, David; Cachicatari, Angela; Cupe-Chacalcaje, Kelly; La Torre-Zuñiga, Alan; Velarde-Acosta, Kevin (Frontiers in Cardiovascular Medicine, 2024)
A 49-year-old female patient, asymptomatic, presented to the cardiology office for a right atrial mass, identified incidentally in a non-electrocardiogram (ECG)-gated contrast-enhanced computed tomography, performed for follow-up of pulmonary tuberculosis. Echocardiography, surprisingly, showed an anechogenic ovoid mass in the right atrium measuring 40 × 40 mm2, implanted in the interatrial septum without affecting the tricuspid valve. ECG-gated computed tomography angiography (CTA), confirmed the dimensions of the mass, which presented homogeneous content, calcified areas, and a 12-mm pedicle implanted near the ostium of the coronary sinus. Additionally, contrast uptake and infiltration of adjacent structures were ruled out. In the surgical field, an encapsulated mass with blood content was found, which pathology reported as a hematic endocardial cyst (HEC). These are rare cardiac masses, constituting 1.5% of all primary cardiac tumors. It is usually an incidental finding, and its clinical presentation will depend on its dimensions and the intracardiac hemodynamic impact. A highlighting feature is its anechogenic content on ultrasound, however, multimodality imaging allows for making diagnostic assumptions, discerning between primary cardiac tumors, and provides morphological and hemodynamic information useful for therapeutic decision making. The age of the patient, the large size of the HEC, and its location in the interatrial septum make up a completely atypical presentation of this rare disease, which motivated this report.